Pengaruh Inflasi dan Investasi terhadap Tingkat Pengangguran di Indonesia - Aprilia Hidayah; tony seno aji (Jurnal Ekonomika : INDEPENDEN, 2022)
Unemployment in daily life is a complex challenge because according to conventional wisdom, a certain task must be performed by humans to get the necessary support to meet their needs. The purpose of his study is to determine the impact of investment and inflation on the rate of reaction in Indonesia. The analytical method used is a quantitative method. Linier regression with diagonal is the analytical technique used. The results of this study indicates that although investment has a positive impact on the reaction rate of unployment in Indonesia, inflation does not have a significant impact on the rate of unemployment.